SHEAR saliva collection device augments sample properties for improved analytical performance - Shang Wei Song; Rashi Gupta; Niharika Jothilingam; Xinlei Qian; Yue Gu; V Vien Lee; Yoann Sapanel; David Michael Allen; John Eu Li Wong; Paul MacAry; Dean Ho; Agata Blasiak (Wiley, 2023)
Abstract Despite being a convenient clinical substrate for biomonitoring, saliva's widespread utilization has not yet been realized. The non‐Newtonian, heterogenous, and highly viscous nature of saliva complicate the development of automated fluid handling processes that are vital for accurate diagnoses. Furthermore, conventional saliva processing methods are resource and/or time intensive precluding certain testing capabilities, with these challenges aggravated during a pandemic. The conventional approaches may also alter analyte structure, reducing application opportunities in point‐of‐care diagnostics. To overcome these challenges, we introduce the SHEAR saliva collection device that mechanically processes saliva, in a rapid and resource‐efficient way. We demonstrate the device's impact on reducing saliva's viscosity, improving sample's uniformity, and increasing diagnostic performance of a COVID‐19 rapid antigen test. Additionally, a formal user experience study revealed generally positive comments. SHEAR saliva collection device may support realization of the saliva's potential, particularly in large‐scale and/or resource‐limited settings for global and community diagnostics.